INTEGRASI CULTURALLY RESPONSIVE TEACHING PADA MODEL PROBLEM-BASED LEARNING: DAMPAKNYA TERHADAP KETERLIBATAN SISWA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Marina Wati; Saiful Bahri; Robiyah Nur (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
This study aims to examine the impact of integrating the Culturally Responsive Teaching (CRT) approach into the Problem-Based Learning (PBL) model on student engagement in Islamic Education (PAI). The primary issue addressed is the low level of student engagement caused by the dominance of conventional methods and a lack of relevance between the material and the students' cultural backgrounds. Utilizing a Quasi-Experimental design with a Posttest-Only Control Group Design, this research involved 69 tenth-grade students at SMKN 8 Bandar Lampung, divided into a control group (36 students) and an experimental group (33 students). Data on student engagement were collected using a questionnaire instrument (15 items, Cronbach's Alpha α = 0,782) and analyzed using an independent sample t-test. The results of the analysis showed a t-value of t = -4,925 with a significance of 0,000 (p < 0,05), and a Mean Difference of 6.414. These findings confirm a significant difference, where the class implementing the PBL-CRT integration demonstrated higher engagement levels compared to the control group. The synergy between problem-solving in PBL and the cultural aspects of CRT is proven to create a more interactive, contextual, and meaningful learning experience. The novelty of this research lies in the integrative application of these two models within the context of Islamic Education at the vocational school (SMK) level. Practically, this study provides a guide for teachers in designing innovative learning strategies capable of enhancing both student engagement and religious understanding in the contemporary era.